Estudio de factibilidad para la creación de un restaurante temático en la ciudad de Manta - Loor Santos, Willians Junior (2024)
The research was conducted with the objective of developing a feasibility study for the creation of a theme restaurant in Manta city, contributing to the diversification of the gastronomic offer in the area. The design of the study was based on four phases. In the first, a market study was carried out that allowed exploring the offer related to restaurant establishments, through an analysis of the various problems, such as the deficiency of a strategic plan, which leads to the closure of restaurants in the short term. In addition, the existing offer was examined, identifying 550 establishments with various themes. The demand profile is characterized by national tourists from different cantons. Regarding the competition, it is found in the restaurants in Manta canton and in Portoviejo canton. In the second phase, a technical study was carried out that included determining the location and engineering of the establishment. Specific areas were defined such as; restaurant, kitchen, parking lots, bar, among others, with a maximum capacity for 60 people. The project design included the development of three process flow charts: service, kitchen and purchasing. The third phase included administrative organization and business planning, with the aim of ensuring the proper functioning of the establishment. Finally, a financial evaluation was carried out that allowed determining the key indicators of economic viability, the Net Present Value of $75,304.28 and an Internal Rate of Return of 33%. These results indicated a higher profitability of the project.